Responses of date Palm Seedling to co-Inoculation with Phosphate Solubilizing Bacteria and Mycorrhizal Arbuscular Fungi - Boutheina, ZOUGARI- ELWEDI; Aya, HDIOUCH; Naima, BOUGHALLEB; Ahmed, NAMSI (International Journal of Environment, Agriculture and Biotechnology, 2019)
With the broad aim of biologically improving P uptake by date palm, in this work we use the beneficial phosphorus solubilizing microorganisms like arbuscular mycorrhizal fungi (AMF) and phosphate solubilizing bacteria (PSB) characterized by a remarkable ability to solubilize phosphorus and tolerance to hard pedoclimatic conditions. For this study, a pot experiment was conducted under greenhouse condition to assess the effect of associations between mycorhizal fungus (Glomus mosseae) (M) with a range of ten bacterial strains (B). An essay of different treatments (control seedlings, seedlings inoculated by arbuscular mycorhizal fungi (AMF) and seedlings inoculated by a combination of PSB and AMF) showed the progressive evolution of microbial activity. The results indicated that the rhizosphere interactions between Glomus mosseae and PSB strains (Pseudomonas striata, Bacillus subtilis) significantly improved growth parameters including root dry weight (23,66%), root length (24%), leaf dry weight (67,7%), leaf length (26,9%), promote P mineralization in soil P (142,3%) uptake by date palm seedling as compared to control, and percent root colonization in date palm seedling was also recorded by the combined inoculation of Glomus mosseae and PSB strains (Pseudomonas striata, Bacillus subtilis).